THE INFLUENCE OF CURRENT RATIO AND ROA ON EPS IN INSURANCE COMPANIES LISTED ON THE IDX - Setyaningrum, Nurfatikha Putri; Rivana, Evin; Ramadhanti, Nadela; Sari, Irsya Husna; Cahya, Hesa Try; Syaflan, Meidi (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This study aims to determine how the influence of Current Ratio (CR) and Return On Assets (ROA) on Earnings Per Share (EPS) partially or simultaneously in Insurance companies listed on the IDX for the period 2017 – 2022. In this study using quantitative research methods and the type of data used is secondary data which is data from the financial statements of insurance sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2022. The population in this study are insurance companies on the Indonesia Stock Exchange (IDX), totaling 15 companies. In this study, the sample selection data for this study were determined by purposive sampling. So the companies sampled in this study totaled 9 insurance companies listed on the Indonesia Stock Exchange from 2017 to 2022. The results of this study indicate that the Variable Current Ratio (CR) has no significant effect on Earning Per Share (EPS) in insurance companies listed on IDX. So the hypothesis in this study can be accepted. The Return On Assets (ROA) variable partially has a significant effect on Earning Per Share (EPS) in insurance companies listed on the IDX. So the hypothesis in this study can be accepted.